Enhancing photocurrent transient spectroscopy by electromagnetic modeling - Diesinger, H. (2013)
The shape and duration of photocurrent transients generated by a photoconductive switch depend on both the intrinsic response of the active material and the geometry of the transmission line structure. The present electromagnetic model decouples both shape forming contributions. In contrast to previously published work, it accounts for the particular operating mode of transient spectroscopy. The objective is to increase the time resolution by two approaches, by optimizing structural response and by deconvolving it from experimental data. The switch structure is represented by an effective transimpedance onto which the active material acts as current generator. As proof of concept, the response of a standard microstrip switch is modeled and deconvolved from experimental data acquired in GaAs, yielding a single exponential material response and hence supporting the validity of the approach. Beyond compensating for the response deterioration by the structure, switch architectures can be a priori optimized with respect to frequency response. As an example, it is shown that a microstrip gap that can be deposited on materials incompatible with standard lithography reduces pulse broadening by an order of magnitude if it is provided with transitions to coplanar access lines.